Determinants of Social Shopping Performance in Small and Medium‐Sized Social Merchants: Theories and Empirical Evidence. (29th December 2013) - Lee, In; Yoo, Sangjin; Choi, Moo‐Jin; Shon, Dal‐Ho; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> In this study, we review theoretical foundations of the social shopping phenomenon and investigate the relationships between key elements of Groupon's social shopping system and sales performance of Groupon promotions. We collected sales and promotion data from Groupon's website for two types of businesses (restaurants and health‐care services) to find the key elements that influence sales for merchants using Groupon's promotions. Our study shows that different types of businesses require different marketing parameters to maximize the number of coupons sold. Implications of our study for social merchants, social intermediaries, and research directions are also discussed.